Análisis de impacto del terremoto de pedernales de 2016 sobre las coordenadas geográficas en hitos IGM seleccionados de Guayaquil - Morocho Plúas, Jorge Washington (2024)
For the realization of this degree project which consists of the Analysis of the impact of the 2016 Pedernales earthquake on the geographic coordinates in selected IGM landmarks of guayaquil, it is presented in the following way: We proceed to obtain existing information of the landmarks already georreferencien, so there are monographs of such control points, creating a route to reach the results and test the hypothesis raised. The methodology that will be used in the development of this research is analyzed, together with the process technique and with the equipment to be used, the population and sample are considered.